Penerapan Prinsip Biomekanika untuk Optimalisasi Performa Atletik Mahasiswa Pendidikan Jasmani - Miftahul Janna; Andi temmassonge; Mohammad Fandi Kurnia (Hybrid: Jurnal Pendidikan dan Pembelajaran Sains, 2025)
This study examines the application of biomechanical principles to optimize athletic performance among physical education students. Biomechanics plays a crucial role in analyzing movement efficiency, reducing injury risk, and improving motor performance, yet its implementation in higher education remains limited. This literature review aims to synthesize empirical findings on how biomechanics contributes to enhancing technique, movement efficiency, and training quality in the context of physical education. A qualitative descriptive approach through library research was employed, drawing on scientific articles published between 2017 and 2025 that discuss biomechanical analysis, athletic performance, injury prevention, and technology-enhanced physical education. The literature search was conducted through Google Scholar, ScienceDirect, SpringerLink, and DOAJ using relevant keywords. The selected studies indicate that biomechanical analysis—such as joint angle evaluation, ground reaction force measurement, and segmental coordination assessment—significantly improves students’ understanding of movement mechanics and supports evidence-based training adjustments. Furthermore, integrating accessible technologies like video-based motion analysis and virtual laboratory tools enhances scientific reasoning and digital literacy among physical education students. However, challenges persist, including limited laboratory facilities, insufficient educator training, and low technological readiness. In conclusion, applying biomechanical principles in physical education offers substantial benefits for optimizing athletic performance, strengthening scientific competence, and supporting modern, technology-oriented learning environments. These findings highlight the need for improved resources and continuous professional development to support sustainable implementation.